Headache and cranial nerve dysfunction secondary to carotid artery aneurysm: two case reports and a literature review - Fortunato, Pedro Neves (2022)
The cavernous sinus is a venous plexus located at the base of the skull. Several pathologies, such as inflammatory, aneurysmal, or metastatic processes, can affect this plexus. Cavernous sinus syndrome occurs when the nerves are involved in this region (cranial nerves III, IV, VI, and divisions of V). These anatomical relationships explain that diplopia and pain are these patients' most common onset symptoms. Carotid cavernous aneurysms (CCAs) account for 2% to 9% of aneurysms. We report two patients who showed cavernous sinus syndrome resulting from carotid artery aneurysms. The recognition of the etiology of this distinguished clinical picture is vital to avoid complications and address the best approach for each patient.